2004
DOI: 10.1161/01.cir.0000136033.21777.4d
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Adenovirus Encoding Adenylyl Cyclase VI Increases Left Ventricular Function in Heart Failure

Abstract: Background-We tested the hypothesis that intracoronary delivery of an adenovirus encoding adenylyl cyclase type VI (Ad.AC VI ) would be associated with increased left ventricular (LV) function in pigs with congestive heart failure. Methods and Results-Pigs (52Ϯ6 kg; nϭ16) underwent placement of pacemakers, LV pressure transducers, and left atrial and aortic catheters. Physiological and echocardiographic studies were obtained from conscious animals 13 days later, and pacing was initiated (220 bpm). Seven days l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 21 publications
(24 reference statements)
0
102
0
Order By: Relevance
“…This model was used in gene therapy studies for angiogenesis and for calcium cycling proteins in dogs, 11,22,23 sheep 7,24,25 and pigs. 26,27 However, left ventricular function is known to partially recover after cessation of pacing without therapy. Thus, it can be challenging to evaluate the efficacy of treatment in some of the cases.…”
Section: Ischemic Heart Failure Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was used in gene therapy studies for angiogenesis and for calcium cycling proteins in dogs, 11,22,23 sheep 7,24,25 and pigs. 26,27 However, left ventricular function is known to partially recover after cessation of pacing without therapy. Thus, it can be challenging to evaluate the efficacy of treatment in some of the cases.…”
Section: Ischemic Heart Failure Modelmentioning
confidence: 99%
“…There are two predominant isoforms of AC in the heart (type 5 and type 6), however the beneficial effect of AC overexpression appears to be limited to AC6. Adenovirus encoding AC6 was injected into coronary arteries of naive 75 and pacing-induced heart failure pigs, 27 and resulted in increased left ventricular contractility. In addition, left ventricular local gene transfer of AC6 has been shown to have the potential to create biological pacemaker after atrioventricular node ablation.…”
Section: Angiogenesismentioning
confidence: 99%
“…The total amount of virus used in these studies is within the range of other intracoronary perfusion studies that did not achieve this level of gene transfer. [25,33,34] The major negative effects observed with this delivery method were decreases in heart rate and blood pressure from the vasodilating agents and a 5% incidence of ventricular arrhythmias during delivery. The frequency of ventricular arrhythmias is a limitation of using the porcine model.…”
Section: Translation To Human Deliverymentioning
confidence: 99%
“…17,18 In previous articles, 17,18 they have established that in murine models of cardiomyopathy, overexpression of the isoform AC VI increases cardiac responsiveness to ␤-adrenergic receptor stimulation (without changes in the amount of the receptor or G-protein), resulting in increased cAMP production and improved cardiac function. In this new study, 19 published in the present issue of Circulation, the authors report a novel therapeutic strategy to treat CHF. They demonstrated that intracoronary delivery of a recombinant adenovirus encoding AC VI (1.4 x 10 12 vp) improves global left ventricular function associated with reduction in LV remodeling in a large animal model of heart failure.…”
Section: Adenylyl Cyclase As the New Therapeuticmentioning
confidence: 99%
“…After gene transfer, improvements in different parameters of LV function were observed, such as reduction in LV end-diastolic and end-systolic dimensions and wall stress, improved systolic wall thickening, increase in LV ϩdP/dt (change in ventricular pressure over change in time) and -dP/dt during stimulation with isoproterenol, increase in cAMP generation, and decrease in plasma concentrations of brain natruretic peptide (a marker of LV dysfunction). A strength of this study 19 is that the authors have chosen a model of CHF that mimics dilated heart failure: Large animals (pigs) subjected to LV pacing and treated only after they displayed obvious signs of heart failure. Their therapeutic approach is clinically relevant and involves an intracoronary administration of genes that is safe, effective, feasible, and non-surgical.…”
Section: Adenylyl Cyclase As the New Therapeuticmentioning
confidence: 99%